2011
DOI: 10.1149/1.3567954
|View full text |Cite
|
Sign up to set email alerts
|

Study of the LiMn1.5Ni0.5O4/Electrolyte Interface at Room Temperature and 60°C

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=18280097&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=18280097&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
128
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 37 publications
(73 reference statements)
3
128
1
Order By: Relevance
“…The traditional LiPF6-based electrolyte often suffers from oxidative decomposition at elevated temperature, and then leads to the formation of unstable solid electrolyte interface (SEI) film on the electrode surface [49,50]. Furthermore, it is easy to make thermal decomposition of LiPF6 salt at elevated temperature, and then react with trace amounts of H2O accompanied by HF formation.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional LiPF6-based electrolyte often suffers from oxidative decomposition at elevated temperature, and then leads to the formation of unstable solid electrolyte interface (SEI) film on the electrode surface [49,50]. Furthermore, it is easy to make thermal decomposition of LiPF6 salt at elevated temperature, and then react with trace amounts of H2O accompanied by HF formation.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions to this problem are centered around finding new optimized electrolyte formulations with new anodically more stable solvents and also additives that can properly passivate the cathode surface the same way they do to the anode. Electrolyte solutions based on molecular solvents with the sulfone functional group, -SO 2 -, were reported by Xu and Angell 6 and Sun and Angell 7 to exhibit a large stability window reaching 5.8 V. Abouimrane et al 8 demonstrated that tetramethylsulfone (TMS) can be used with ethyl-methyl carbonate (EMC) as co-solvent and LiPF 6 as salt in Li 4 Ti 5 O 12 /LiMn 1.5 Ni 0.5 O 4 full cells and reported good capacity. Sulfones, however, are not stable against graphitic carbon anodes and have in general a relatively high melting point (25 • C for TMS) and viscosity, limiting their room temperature and high-rate battery performance.…”
mentioning
confidence: 99%
“…The use of TFSI − anion however limits the high voltage application of this particular mixture because it corrodes aluminum, the current collector for the cathode. Isken et al reported that LiTFSI could be successfully substituted by LiBF 4 12 in a binary electrolyte solution consisting of 0.9 M LiBF 4 EC:ADN 1:1 and was cycled in LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM, 4.3 V) cathode or graphite anode half cells for 50 cycles with low capacity fade and high coulombic efficiency. Nagahama et al 13 reported earlier that the electrolyte solution can be modified by adding dimethyl carbonate (DMC) to decrease the viscosity and increase the conductivity and still be stable up to 7 V. This ternary electrolyte solution was prepared for dinitrile solvents with chain length n = 3 (Glutaronitrile) up to n = 10 (Dodeconitrile).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five cycles were repeated at each C-rate: C/12, C/6, C, 2 C, 5 C, and back to C/12 again to check for any capacity fade after high C-rate cycling. During the first 10 cycles (at C/12 and C/6), capacity fade of 6% was observed that is commonly associated with increased resistances at the interface and the bulk electrode, with the former being more significant in this case due to the high surface area of the material [31]. After the tenth cycle, the capacity was stabilized and also recovered at low C-rate (C/12) with a 12% loss from the initial capacity (158 mAh g −1 ).…”
Section: Resultsmentioning
confidence: 98%